Exploring the Opportunities and constraint of E-Commerce Technology implementation Among Afghan Entrepreneurs - Barialay Raufi; Amir Kror Shahidzay (Department of Informatics, Universitas Malikussaleh, 2026)
This study investigates the opportunities and barriers associated with e-commerce technology adoption among Afghan entrepreneurs operating in a fragile, infrastructure-constrained economy. A quantitative, descriptive research design was employed using a structured, Technology Acceptance Model-based questionnaire distributed through Google Forms to online traders and technology professionals in Kabul City and several provincial centers. Of 410 individuals contacted, 210 valid responses were obtained (N = 210), and the instrument demonstrated high internal consistency (Cronbach's alpha = 0.812). Descriptive statistics, multiple linear regression, ANOVA and Pearson correlation were computed using SPSS. The results show near-universal recognition of technology as an opportunity for business growth (99.1%), competitiveness (97.2%) and time savings (96.2%), with social media platforms serving as the dominant commercial channel (93.3%). At the same time, respondents reported severe structural barriers: absence of internet in remote areas (94.7%), weak cybersecurity (91.9%), high connectivity costs (91.9%), low public trust (88.6%) and limited digital awareness (88.1%). Regression analysis showed that perceived technology benefits explained only 19.0% of the variance in business growth (R² = 0.190), while barrier factors explained 10.1% (R² = 0.101). Correlation analysis identified technology impact as the strongest predictor of growth (r = 0.670), while technical weaknesses and technology-skill gaps were very strongly correlated (r = 0.814). The findings suggest that infrastructure investment, cybersecurity legislation and digital-literacy programs are prerequisites for translating entrepreneurial enthusiasm into measurable e-commerce growth in Afghanistan.